2017
DOI: 10.1364/oe.25.028914
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scattering limit in optical microscopy

Abstract: Optical microscopy offers a unique insight of biological structures with a sub-micrometer resolution and a minimum invasiveness. However, the inhomogeneities of the specimen itself can induce multiple scattering of light and optical aberrations which limit the observation to depths close to the surface. To predict quantitatively the penetration depth in microscopy, we theoretically derive the single-to-multiple scattering ratio in reflection. From this key quantity, the multiple scattering limit is deduced for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Nevertheless, measurements of l′ (reF. 10 ) and the analytical estimation of the ratio between the SS wave and MS waves 11 have provided insight into the interaction between these factors. The remaining MS waves are described by E τ τ k ( ; ≠ ) DC o 0 and travel along longer or shorter path lengths than that of the SS wave and thus have different flight times.…”
Section: Deep Optical Imaging Within Complex Scattering Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, measurements of l′ (reF. 10 ) and the analytical estimation of the ratio between the SS wave and MS waves 11 have provided insight into the interaction between these factors. The remaining MS waves are described by E τ τ k ( ; ≠ ) DC o 0 and travel along longer or shorter path lengths than that of the SS wave and thus have different flight times.…”
Section: Deep Optical Imaging Within Complex Scattering Mediamentioning
confidence: 99%
“…2 should be >1, which sets the gating limit (solid blue line in the figure) for typical aberration-free optical coherence microscopy equipped with temporal, confocal and polarization gating 10,11 . Both the dynamic range and gating limits are affected by factors such as the spatial resolving power, temporal gating width and the scattering parameters of the scattering medium.…”
Section: Imaging Through a Scattering Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that aberrations in the sample arm do not influence the transverse resolution in FF-OCT using spatially incoherent light [20]. Recently, a method based on the measurement of the reflection matrix has demonstrated an efficient discrimination between singly and multiply scattered light, with an unprecedented increase in the OCT working depth [21], thus pushing the limits of optical microscopy in highly scattering media [22].…”
Section: Introductionmentioning
confidence: 99%
“…Even with these substantial advances, the imaging depth of high-resolution optical microscopy has not yet reached the detection limit set by the dynamic range of state-of-the-art sensor technology. The ballistic wave is, in principle, detectable even at depths >15 l s in an epi-detection geometry (where l s is the scattering mean free path of the scattering medium) if an image sensor of high dynamic range (e.g., 1:10 4 ) is used in conjunction with interferometric detection converting an intensity recording into an electric field measurement 10,12,13,18,19 . Currently, the imaging depth limit is instead set by the competition between the ballistic wave and the multiply scattered wave that bypasses the existing gating operations.…”
mentioning
confidence: 99%